Tissue Cardiomyoplasty Using Bioengineered Contractile Cardiomyocyte Sheets to Repair Damaged Myocardium: Their Integration with Recipient Myocardium - Shigeru Miyagawa; Yoshiki Sawa; S Sakakida; Satoshi Taketani; Haruhiko Kondoh; Imran Memon; Yukiko Imanishi; Tatsuya Shimizu; Teruo Okano; Hikaru Matsuda (2005)
Background. We hypothesized that tissue-engineered contractile cardiomyocyte sheets without a scaffold would show histological and electrical integration with impaired myocardium, leading to the regeneration of infarcted myocardium. Methods. Neonatal rat cardiomyocytes were cultured on Poly(N-isopropylacrylamide)-grafted polystyrene dishes and detached as a square cell sheet at 20°C. Two sheets were stacked to make thicker contractile cardiac sheets. In cross-section, the stacked sheets looked like homogeneous heart-like tissue. Two weeks after rats were subjected to left anterior descending (LAD) ligation, two treatments were conducted: 1) cardiomyocyte sheet implantation (T group, n=10), and 2) fibroblast sheet implantation (F group, n=10). The control group underwent no additional treatment (C group, n=10). Results. Echocardiography demonstrated that cardiac performance was significantly ameliorated in the T group 2, 4, and 8 weeks after implantation. The cardiomyocyte sheets became attached to the infarcted myocardium, showed angiogenesis, expressed connexin-43, and appeared as homogeneous tissue in the myocardium Electrophysiological experiments showed a QRS complex with one peak in the treated scar area in the T group, but two peaks, indicative of branch block, in that of the other groups. Furthermore, the threshold for pacing of the recipient heart was lower in the T group than in the other groups. Conclusions. Cardiomyocyte sheets integrated with the impaired myocardium and improved cardiac performance in a model of ischemic myocardium. Techniques using such tissue-engineered cell sheets are introducing the promising concept of tissue cardiomyoplasty to the field of regenerative medicine.